Neighborhood social cohesion and obesity in the United States - Dana M. Alhasan; Symielle A. Gaston; Lauren R. Gullett; W. Braxton Jackson, II; Fatima Cody Stanford; Chandra L. Jackson (Endocrine and Metabolic Science, 2023)
Low neighborhood social cohesion (nSC) has been associated with obesity. Still, few studies have assessed the nSC-obesity relationship among a large, nationally representative, and racially/ethnically diverse sample of the United States population. To address this literature gap, we examined cross-sectional associations among 154,480 adult participants of the National Health Interview Survey (NHIS) from 2013 to 2018. We also determined if associations varied by race/ethnicity, sex/gender, age, annual household income, and food security status. Based on a 4-item scale from the Project on Human Development in Chicago Neighborhoods Community Survey, we categorized nSC as low, medium, and high. Based on body mass index (BMI) recommendations, we categorized obesity as ≥30 kg/m2. We used Poisson regression with robust variance to directly estimate prevalence ratios (PRs) and 95 % confidence intervals (CIs) while adjusting for sociodemographic characteristics, such as annual household income, educational attainment, and marital status, along with other confounders. Study participants' mean age ± standard error was 47.1 ± 0.1 years; most (69.2 %) self-identified as Non-Hispanic (NH)-White; and 51.0 % were women. NH-Black and Hispanic/Latinx adults comprised more of the population in neighborhoods with low nSC (14.0 % NH-Black, 19.1 % Hispanic/Latinx, and 61.8 % NH-White) versus high nSC (7.7 % NH-Black, 10.4 % Hispanic/Latinx and 77.0 % NH-White). Low vs. high nSC was associated with a 15 % higher prevalence of obesity (PR = 1.15 [95 % CI: 1.12–1.18]), and the magnitude of the association was more substantial among NH-White adults (PR = 1.21 [95 % CI: 1.17–1.25]) compared to associations among Hispanic/Latinx (PR = 1.04 [95 % CI: 0.97–1.11]) and NH-Black (PR = 1.01 [95 % CI: 0.95–1.07]) adults. Low vs. high nSC was associated with a 20 % higher prevalence of obesity in women (PR = 1.20 [95 % CI: 1.16–1.24]) compared to a 10 % higher prevalence in men (PR = 1.10 [95 % CI: 1.06–1.14]). Low vs. high nSC was associated with a 19 % higher prevalence of obesity among adults ≥50 years old (PR = 1.19 [95 % CI: 1.15–1.23]) compared to a 7 % higher prevalence of obesity among adults <50 years old (PR = 1.07 [95 % CI: 1.03–1.11]). Efforts to address nSC may improve health and address health disparities.